Influence of Mg Addition on Crystallisation Kinetics and Structure of the Zn-Al-Cu Alloy - Krupiński M.; Labisz K.; Tański T.; Krupińska B.; Król M.; Polok-Rubiniec M. (Archives of Metallurgy and Materials, 2016)
In this work the effect of Mg addition on structure as well as kinetics of crystallisation of Zn-Al-Cu cast alloy was presented. To the zinc alloy was added 0.1% mass of Mg. The alloy was cast into a metal mould. Thermo-derivative analysis was performed using the UMSA platform (Universal Metallurgical Simulator and Analyzer). The investigated alloys were freely cooled down with a rate of 0.1°C s-1. For the structure analysis were used results obtained using light microscopy, scanning and transmission electron microscopy.